2023
DOI: 10.1097/brs.0000000000004588
|View full text |Cite
|
Sign up to set email alerts
|

Lower Neighborhood Socioeconomic Status May Influence Medical Complications, Emergency Department Utilization, and Costs of Care After 1-2 Level Lumbar Fusion

Abstract: Study Design. Retrospective Case-Control Study. Objectives. The objectives were to determine whether patients from poor social determinants of health, undergoing primary 1- to 2-level lumbar fusion, demonstrate differences in (1) medical complications, (2) emergency department (ED) utilizations, (3) readmission rates, and (4) costs of care. Summary of Background Data. Measures of socioeconomic disadvantage may enable improved targeting and prevention of potentially increased health care utilization. The Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…In the ADI-based studies that examined dollar amounts for these spending outcomes from claims data, total spending for surgical care (including postacute care and readmissions) for 4 common surgeries was $2654 higher among those in the highest ADI quintile compared with the lowest, and index hospitalization spending associated with general surgery cases was $1811 higher for those in the highest ADI quartile . Overall 90-day spending following a surgical procedure was $3003 to $7415 higher among patients from the highest-decile ADI areas . Total annual spending for Medicare beneficiaries in Maryland was $3519 higher in the highest ADI quintile compared with the lowest and $48 more per point increase in national ADI percentile for Medicare beneficiaries nationally .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the ADI-based studies that examined dollar amounts for these spending outcomes from claims data, total spending for surgical care (including postacute care and readmissions) for 4 common surgeries was $2654 higher among those in the highest ADI quintile compared with the lowest, and index hospitalization spending associated with general surgery cases was $1811 higher for those in the highest ADI quartile . Overall 90-day spending following a surgical procedure was $3003 to $7415 higher among patients from the highest-decile ADI areas . Total annual spending for Medicare beneficiaries in Maryland was $3519 higher in the highest ADI quintile compared with the lowest and $48 more per point increase in national ADI percentile for Medicare beneficiaries nationally .…”
Section: Resultsmentioning
confidence: 99%
“…24 Overall 90-day spending following a surgical procedure was $3003 to $7415 higher among patients from the highest-decile ADI areas. 25,30 Total annual spending for Medicare beneficiaries in Maryland was $3519 higher in the highest ADI quintile compared with the lowest 18 and $48 more per point increase in national ADI percentile for Medicare beneficiaries nationally. 19 In a study using Medicare fee-for-service claims from New York City-area health systems, residence in the highest ADI quintile was associated with similar total Medicare spending but $53 or 12% higher potentially preventable spending than residence in the middle quintile.…”
Section: Health Care Spending Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…First, socioeconomic status (SES) stands out as a potential confounder in the association between the type of surgical center (FASC or HOSC) and postoperative ED visits. SES is known to influence both the likelihood of ED visits postoperatively and the accessibility and location of ambulatory surgery centers . We believe the study could have been strengthened by adjusting for SES, possibly using the hospital zip code data available in the Healthcare Cost and Utilization Project database, or by incorporating other SES-related variables if more granular data were accessible.…”
mentioning
confidence: 99%
“…They found that patients with depression did worse than patients with a BMI > 35 kg/m 2 . A study on 28,410 shoulder arthroplasties [1] likewise found that depressive disorders are associated with longer lengths of stay and more complications, and another study [2] found that preoperative depression screening decreased complications and healthcare costs in lumbar fusion. Another striking finding of this study [4] was that patients who had multiple-joint arthritis also reported poorer outcomes.…”
mentioning
confidence: 99%